Step-by-step explanation:
5+6x=2x-7
We simplify the equation to the form, which is simple to understand
5+6x=2x-7
We move all terms containing x to the left and all other terms to the right.
+6x-2x=-7-5
We simplify left and right side of the equation.
+4x=-12
We divide both sides of the equation by 4 to get x.
x=-3
Convert them into fractions
i)-2 3/8 = -19/8
ii)0.75 = 75/100 = 3/4
iv) 1 3/4 = 7/4
Now convert all of them in the form of p/q where q = 8
Therefore
ii)6/8
iv) 14/8
Answer:
Step-by-step explanation:
Solve the system:
8x−4y=20
4x−8y=4
Reduce the first equation by dividing every term by -2:
-4x + 2y = -10
and then combine this result with the second equation:
4x−8y=4
-4x + 2y = -10
--------------------
-6y = -6, and so y = 1.
According to the first equation, if y = 1, then 4x - 8 = 4, or x = 3.
Then x = 3 and y = 1.
So, finally, x - y = 3 - 1 = 2
Answer:
2.33944954128
Step-by-step explanation:
Answer:
add 1 Century to divide £6 000 000